Isolation of pure strains of Babesia bovis, Babesia bigemina and Anaplasma marginale in an enzootic area - Kessler, Raul Henrique; Madruga, Cláudio Roberto; Jesus, Elane Fabricio de; Semprebom, Domingos Vieira (Pesquisa Agropecuaria Brasileira, 2014)
Pure strains of Babesia bovis and Babesia bigemina were isolated by placing larvae and numphs respectively of the tick Boophilus microplus, on splenectomized calves. Anaplasma marginale was isolated by the inoculation of blood from a bovine carrier into a splenectomized calf, followed by medication with a babesicide. Larvae transmitted B. bovis only when removed from the calf on the fifth day of infestation. However, B. bigemina was transmitted when ticks were removed on the sixth day. Nymphs and adults transmitted only B. bigemina. No transmission of Anaplasma by larvae, nymphs or adults occurred.